E-Dengie Teleconsultation System - Maria Soosai, Beatrice Ann (2011)
This research towards providing a framework of integrated solution in managing the disease. Thus, a system called \"e-dengue Teleconsultation\" will be build to allow user (patient) to get early concern about the disease, and to do follow up consultation. In this proposed teleconsultation system image, text and voice can also be interchanged via mobile hand phone.